11
Аноним
Математика
04 июня 12:33

(x-2y)²+6xy (3ab³)²·(a³b)²

Ответ или решение1

Селиверстов Виталий

Упростим выражения:

1) (x - 2 * y)² + 6 * x * y; 

Раскроем скобки применяя формулу сокращенного умножения и приведем подобные значения.  

(x - 2 * y)² + 6 * x * y = x² - 2 * x * 2 * y + (2 * y)² + 6 * x * y = x² - 4 * x * y + 4 * y² + 6 * x * y = x² + 2 * x * y + 4 * y²;  

Значит, (x - 2 * y)² + 6 * x * y = x² + 2 * x * y + 4 * y². 

2) (3 * a * b³)² * (a³ * b)² = 3^2 * a^2 * (b^3)^2 * (a^3)^2 * b^2 = 9 * a^2 * b^(3 * 2) * a^(3 * 2) * b^2 = 9 * a^2 * b^6 * a^6 * b^2 = 9 * a^(2 + 6) * b^(6 + 2) = 9 * a^8 * b^8; 

(3 * a * b³)² * (a³ * b)² = 9 * a^8 * b^8. 

 

0 / 10000
ВходРегистрация

Вход

или

Регистрация